DESIGN OF PARALLEL COUPLED LINES BANDPASS FILTER USING DEFECTED GROUND STRUCTURE - SYAZA SYAFIQAH, ZAIDAN (Universiti Malaysia Sarawak, (UNIMAS), 2020)
Filter is a prominent component due to its ability to remove unwanted signal components with the specified frequency range in a signal transmission. The parameters of a filter which includes the gain and the efficiency have to be sufficiently optimised in order to produce the best signal outcome. A range of spurious frequency can cause the operating frequency in the signal for the transmission to undergo distortion thus causing inaccuracy in the filter. Therefore, to overcome this problem, an improvement on a Parallel Coupled Lines Bandpass Filter is designed with the implementation of Defected Ground Structure (DGS) design on the ground plane of the filter to elevate the performance. Parallel Coupled lines Bandpass Filter is proposed in order to achieve optimum results such as the attenuation and the reduction of losses abilities in the filter. The filter is simulated by using Rogers RO4003C and RO4350B substrate materials with a dielectric material of 3.38 and 3.66 and substrate thickness of 0.813mm and 0.762mm respectively. An operational frequency of 5.8GHz based on the ISM band is targeted. Multiple DGS structures are proposed and the most ideal among the etched designs is selected as the resonant structure in the ground plane of the filter. By properly adjusting the dimensions and position of the DGS shape, the H-shaped DGS filter design is selected as the losses the selectivity of the designed filter is significantly improved from the conventional design. The result of the filter’s losses are simulated by using the simulation software, Advanced Design Software (ADS) and the H-shaped DGS filter design with the insertion loss (S21) of -1.412dB and the return loss (S11) of -20.24dB are measured by using Vector Network Analyzer (VNA) after the fabrication process.